Characterization of NS5A polymorphisms and their impact on response rates in patients with HCV genotype 2 treated with daclatasvir-based regimens. (7th September 2016) - Zhou, Nannan; Han, Zhou; Hartman-Neumann, Sandra; DeGray, Brenda; Ueland, Joseph; Vellucci, Vincent; Hernandez, Dennis; McPhee, Fiona
Abstract : Objective: Daclatasvir (DCV) is a pan-genotypic non-structural protein 5A (NS5A) inhibitor that is approved for treatment of hepatitis C virus (HCV) genotype (GT)1 and GT3 in the USA and GT1, GT3 and GT4 in Europe. We set out to examine the impact of daclatasvir-based regimens on the sustained virologic response (SVR) in patients with GT2 infection with respect to GT2 subtype and NS5A polymorphisms at amino acid positions associated with daclatasvir resistance. Methods: Analyses were performed on 283 GT2 NS5A sequences from five daclatasvir regimen-based clinical trials (ClinicalTrials.gov: NCT-01257204, NCT-01359644, NCT-02032875, NCT-02032888 and NCT-01616524) and 143 NS5A sequences from the Los Alamos HCV database. Susceptibility analyses of substitutions at amino acid positions associated with daclatasvir resistance and patient-derived NS5A sequences were performed using an in vitro HCV replication assay. Results: Of 13 GT2 subtypes identified from 426 NS5A sequences, the most prevalent were GT2a (32%), GT2b (48%) and GT2c (10%). The most prevalent NS5A polymorphism was L31M (GT2a = 88%; GT2b = 59%; GT2c = 10%). Substitutions identified in 96% of GT2 NS5A sequences exhibited daclatasvir EC50 values ranging from 0.005 to 20 nM when tested in vitro . A similar range in daclatasvir EC50 values was observed for 16 diverse GT2 patient-derived NS5A sequences (EC50  = 0.005–60 nM). Depending on the daclatasvir-based regimen studied (daclatasvir/interferon-based or daclatasvir/sofosbuvir-based), SVR rates ranged from 90% to 100% in GT2 patients with the most prevalent baseline NS5A-L31M polymorphism, compared with from 96% to 100% without this polymorphism. Conclusions: High SVR rates were achieved in patients infected with GT2 treated with daclatasvir-based regimens irrespective of GT2 subtype or baseline NS5A polymorphisms.